Thyrotropin (TSH) Receptor Residue E251 in the Extracellular Leucine-Rich Repeat Domain Is Critical for Linking TSH Binding to Receptor Activation - Chen, Chun-Rong (The Endocrine Society, 2010)
The TSH receptor (TSHR) ectodomain comprises a tubular leucine-rich repeat domain (LRD) and a hinge [or signaling specificity domain (SSD)]. TSH binds to both the LRD and SSD, leading to signal transduction by the transmembrane domain. The SSD structure and spatial orientation to the other components are unknown. We exploited a fortuitous observation to obtain mechanistic insight into the relationship between TSH binding and signal transduction. A mouse TSHR cDNA generated by PCR was found to express a receptor with poor TSH-induced cAMP generation despite normal TSH binding. Progressive reversion to wild-type of six mutations revealed E251K in the LRD to be critical for reduced signal transduction in both mouse and human TSHR. An I286F substitution in the SSD had a much weaker effect and was additive with E251K. To our knowledge, there are no previous examples of specific amino acid mutations in the TSHR LRD that dissociate TSH binding from TSHR signal transduction. To prevent flailing of the TSHR LRD, its position vis-à-vis the SSD must be stabilized by multiple amino acid interactions. The present data suggest that TSHR residue E251 is one of these residues involved in stabilizing the LRD relative to the SSD, thereby enabling ligand binding to transduce a signal by the latter. That the E251K mutation can reduce signal transduction despite high-affinity TSH binding comparable with the wild-type TSHR provides mechanistic insight into the coupling between ligand binding and receptor activation.